Dimensionless Analysis on the Characteristics of Pneumatic Booster Valve with Energy Recovery. (27th October 2016) - Yang, Fan; Tadano, Kotaro; Li, Gangyan; Kagawa, Toshiharu
Abstract : Factories are increasingly reducing their air supply pressures in order to save energy. Hence, there is a growing demand for pneumatic booster valves to overcome the local pressure deficits in modern pneumatic systems. To further improve energy efficiency, a new type of booster valve with energy recovery (BVER) is proposed. The BVER principle is presented in detail, and a dimensionless mathematical model is established based on flow rate, gas state, and energy conservation. The mathematics model was transformed into a dimensionless model by accurately selecting the reference values. Subsequently the dimensionless characteristics of BVER were found. BVER energy efficiency is calculated based on air power. The boost ratio is found to be mainly affected by the operational parameters. Among the structural ones, the recovery/boost chamber area ratio and the sonic conductance of the chambers are the most influential. The boost ratio improves by 15%–25% compared to that of a booster valve without an energy recovery chamber. The efficiency increases by 5%–10% depending on the supply pressure. A mathematical model is validated by experiment, and this research provides a reference for booster valve optimisation and energy saving.